Mineral resources and development - Roonwal, G. S. (Ganpat Singh) 1940-.; Shahriar, K.; Ranjbar, H. (Hojjatollah) 1964-.; Centre for Science and Technology of the Non-Aligned and Other Developing Countries (Delhi Daya Pub. House, 2005)
Contributed papers presented in an international workshop on "Mineral Resources and Development" jointly organized by Centre for Science and Technology of the Non-Aligned and Other Developing Countries and Department of Mining Engineering, Shahid Bahonar University of Kerman, Iran between 1-4 July, 2004; with reference to South Asia, Middle East, and North Africa.
"Centre for Science and Technology of the Non-Aligned and Other Developing Countries (NAM S&T Centre)."
Keywords: Mineral industries -- Developing countries -- Congresses; Mines and mineral resources -- Developing countries -- Congresses; Developing countries -- Economic conditions -- Congresses